Acid and heat fastness in microsporidia: How acid fast are acid fast microsporidium?. (21st January 2020) - Mittal, Ruchi; Agarwal, Sunil; Muduli, Kalandi Ch; Sahu, Srikant; Das, Sujata
Abstract: Microsporidia are obligate spore-forming microorganisms with strong resemblance to fungi and can affect almost every organ system in immunocompetent or immunocompromised individuals. Mixed infections are also reported in immunocompromised hosts. Microsporidial spores show marked morphological variations and the small and slender forms can resemble bacilli. Modified Zeihl Neelsen (ZN) stain, cold method demonstrates them as bright red in color, leaving several spores blue or incompletely stained; thus, they are reported as weakly or variably acid fast. Variability in staining results with ZN stain and considering the fact that Mycobacterium tuberculosis, the commoner bug in developing countries is identified by its resistance to stronger acids on ZN staining, authors wished to demonstrate acid and heat fastness in microsporidium using corneal tissue specimens. Microsporidial spores stained bright red in color with conventional ZN stain, demonstrated strong acid fastness, and interestingly the staining results improved on heating. Thus, the authors conclude that they are strongly acid and heat fast and care must be warranted so that they are not misdiagnosed as Mycobacterium or other acid-fast organisms. Careful observation of morphology, battery of special stains, and molecular diagnostics should be advocated for diagnostic confirmation. To the best of the authors' knowledge, this is the first explicit report on acid and heat fastness on microsporidial spores.